Loneliness, Parasocial Interaction, and the Media: Tracing the Patterns of Understanding - Johnson, Kevin (Université d'Ottawa | University of Ottawa, 2015)
This study examines a predominant trend in the literature regarding communication and media effects. The purpose of the current study is to examine the extent to which this pattern is identifiable in the communication and media literature that has focused on parasocial interaction and loneliness over the past 65 years. The central argument of this study is that this pattern may result in a field of research that is not growing at an optimal rate, and that the recognition of this problem is the first step towards its resolution. The argument advanced in this study relies upon a chronological review and thematic discussion of the parasocial interaction and loneliness literatures published between 1950 and 2015 in North America. Three central themes emerge through the review: ubiquitous contention, the application of repetitive arguments to newer media technologies, and the resilient camps of perspective.